2003
DOI: 10.1164/rccm.200202-080oc
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps Fatigability after Single Muscle Exercise in Patients with Chronic Obstructive Pulmonary Disease

Abstract: The purpose of this study was to compare quadriceps fatigability in patients with varying severity of chronic obstructive pulmonary disease with age-matched control subjects. Ten healthy control subjects, 8 patients with severe disease (FEV1 less than 35% predicted), and 11 patients with mild to moderate disease were studied. The FEV1 was 1.75 +/- 0.13 L (SE), 50.4 +/- 2.9% of predicted in the mild to moderate group, and 0.87 +/- 0.06 L, 25.9 +/- 1.9% of predicted in the severe group. Quadriceps fatigue was qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 28 publications
4
69
1
2
Order By: Relevance
“…15 Unlike those observed in the lower limb muscles, alterations in fiber-type distribution and decreased metabolic capacity do not seem to be involved in early fatigue of the upper limb muscles. This assertion is based on previous studies that demonstrated preserved or even increased oxidative capacity, 7 as well as a concomitant presence of the normal, atrophic, and hypertrophic pattern of fibers within the middle deltoid, when compared to a control group. 15 Although widely used for evaluation of muscle fatigue, submaximal sustained isometric contraction [40][41][42][43][44] has the disadvantage of being dependent on motivation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…15 Unlike those observed in the lower limb muscles, alterations in fiber-type distribution and decreased metabolic capacity do not seem to be involved in early fatigue of the upper limb muscles. This assertion is based on previous studies that demonstrated preserved or even increased oxidative capacity, 7 as well as a concomitant presence of the normal, atrophic, and hypertrophic pattern of fibers within the middle deltoid, when compared to a control group. 15 Although widely used for evaluation of muscle fatigue, submaximal sustained isometric contraction [40][41][42][43][44] has the disadvantage of being dependent on motivation.…”
Section: Discussionmentioning
confidence: 96%
“…These changes increase the fatigability of the quadriceps femoris, which has been demonstrated in both dynamic 5,6 and isometric contractions. 7 For the upper limbs a variety of muscles have been studied, making it difficult to generalize upper limb performance results. 2,8 Because of the finding that the isometric handgrip force is conserved in patients with COPD, some studies infer that the upper limb function is preserved.…”
Section: Introductionmentioning
confidence: 99%
“…As such, they suggest that factors other than atrophy might play a role in explaining skeletal muscle dysfunction in COPD patients (Malaguti et al 2006). Their position is supported by several reports that have documented the presence of intrinsic abnormalities inside limb muscle fi bers of COPD patients, especially in the form of contractile fatigue (Mador et al 2000(Mador et al , 2001(Mador et al , 2003a(Mador et al , 2003bSaey et al 2003Saey et al , 2005Saey et al , 2006. A good example of these reports is that of Mador and colleagues (Jeffery et al 2000) who found a signifi cant decrease in quadriceps twitch force of patients with severe COPD -by more than 20% within 30min of termination of exercise -a value that was signifi cantly greater than that observed in control subjects.…”
Section: Muscle Fi Ber Atrophymentioning
confidence: 86%
“…A primary factor leading to muscular fatigue could be related to abnormal skeletal muscle structureandfunction,which,inCOPD,includesabnormal cellmassalterations,muscularproteindegradationleading tomusclewasting/atrophy,impairedenergyproduction andmetabolicperformance,andincreasedsusceptibility tomusclefatigueandweakness. [12][13][14][15][16][17][18][19][20] GaitalterationsinpatientswithCOPDarelikelysecondarytoalteredskeletal musclestructureandfunction.Mechanismsleadingto alteredskeletalmusclestructureandfunctioninCOPD are uncertain and are not clearly delineated. Disuse and/or systemic inflammation are believed to play a role.…”
Section: Introductionmentioning
confidence: 99%